2019
DOI: 10.1039/c9ra02617g
|View full text |Cite
|
Sign up to set email alerts
|

[Cu(POP)(N^S)][PF6] and [Cu(xantphos)(N^S)][PF6] compounds with 2-(thiophen-2-yl)pyridines

Abstract: [Cu(P^P)(N^S)][PF6] with N^S = 2-(thiophen-2-yl)pyridines show close cation⋯anion association in the solid-state; complex cation association with Cl− occurs in solution. The compounds are blue-emitters in solution with a red-shift of the emission on going to the solid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…This compound was incorporated as the electroluminophore in a LEC, but exhibited poor EL and poor charge transporting properties. 139 The neutral complex [Cu(dppb) (35)] (dppb = 1,2bis(diphenylphosphano)benzene) is a green emitter. In the solid state,  max em (PL) = 521 nm and PLQY = 52% at 293 K, and the corresponding values at 77 K are 534 nm and 73%, with an increased decay lifetime on cooling.…”
Section: Mononuclear [Cu(p^p)(n^s)] + and [Cu(p^p)(p^s)] +mentioning
confidence: 99%
“…This compound was incorporated as the electroluminophore in a LEC, but exhibited poor EL and poor charge transporting properties. 139 The neutral complex [Cu(dppb) (35)] (dppb = 1,2bis(diphenylphosphano)benzene) is a green emitter. In the solid state,  max em (PL) = 521 nm and PLQY = 52% at 293 K, and the corresponding values at 77 K are 534 nm and 73%, with an increased decay lifetime on cooling.…”
Section: Mononuclear [Cu(p^p)(n^s)] + and [Cu(p^p)(p^s)] +mentioning
confidence: 99%
“…† The DFT bond length data were found to be longer than the corresponding X-ray reported values by only 0.01-0.1Å (ref. [35][36][37][38] (Table S2 †) which may have been attributed to the DFT calculations, a single molecule in gaseous state was considered and so no intermolecular coulombic interactions, while the X-ray obtained for molecules in solid state interacting in crystal lattice. 39 The dihedral angle data of the cationic picolinamidines 4a-c showed that the pyridyl ring was titled on the thienyl moiety plane by 3.00-4.50 , i.e.…”
Section: Computational Studiesmentioning
confidence: 99%
“…Both thienyl and phenyl rings bond angle data of the investigated cationic picolinamidines almost coincided with those obtained from X-ray single crystal of analogue compounds. [35][36][37][38] For example, cationic compound 4c data showed that C 4 40 respectively, and their energy explain the ultimate charge transfer. 41,42 Moreover, the HOMO-LUMO energy gap decrease shows the ease of charge transfer interactions, which may be responsible for the bioactivity of the molecules.…”
Section: Computational Studiesmentioning
confidence: 99%
See 2 more Smart Citations